Competition in a Multimarket Environment: The Case of Market Exit - Boeker, Warren; Goodstein, Jerry; Stephan, John; Murmann, Johann Peter (Organization Science, 1997)
Studies of competition typically have two underlying assumptions: that competition occurs within the boundaries of industries or markets and that all firms in a market or industry are affected equally by competitive pressures. The concept of multipoint competition challenges both assumptions. Multipoint theory addresses how different levels of contact between firms across multiple markets affect competition in individual markets. Its main argument is that high levels of contact between firms across markets will induce mutual forbearance, causing multipoint competitors to refrain from aggressively attacking each other. The restraint stems from the fact that high levels of intermarket contact enable a firm to respond to an aggressive action by a multipoint rival in markets other than the one in which the action takes place. That possibility raises the potential costs of aggressive moves and serves as a credible deterrent, especially if a firm can respond in several markets. In addition, multipoint competition helps firms to interpret their rivals' intentions and signal their own, reducing the likelihood of costly misunderstandings. The authors elaborate on those ideas to examine how a hospital's degree of intermarket contact with its competitors in a particular service market affects the likelihood that it will exit that market. They find that hospitals are less likely to exit markets in which they meet large numbers of their multipoint rivals. As a result of mutual forbearance, competitive rivalry is reduced across the markets that multipoint rivals share, lessening the types of pressures that typically prompt market exit. With lower levels of competitive rivalry, markets shared by multipoint rivals are relatively more hospitable environments in which to operate and are less likely to be exited. Rather than competing intensely, multipoint rivals appear to adopt a “live and let live” approach toward each other. The fact that multipoint contact across markets may lessen competitive pressures within individual markets has implications for the contact between firms in several settings. Multimarket contact can occur across different product or service markets and also across different geographic markets, thus affording an intriguing perspective for the investigation of the rivalry between emerging transnational firms. True transnationals, by successfully integrating global operations while still addressing local market concerns, have been seen by some as having the capabilities necessary for successful performance in international competition. Perhaps transnational firms, because they have an integrated decision-making structure, can coordinate their actions to reduce competitive rivalry with each other across the markets they share. If so, markets dominated by transnationals may become more stable than the current state of international competition would predict.